Scaling your startup : mastering the four stages from idea to $10 billion - Cohan, Peter S. (Apress, 2019)
Know how your company can accelerate growth by not only tapping into new growth vectors, but also by adapting its organization, culture, and processes. To oversee growth from an idea to a company with billions in revenue, CEOs must reinvent many aspects of their company in anticipation of it reaching ever-higher revenues. Author Peter Cohan takes you through the four stages of scaling: winning the first customers, building a scalable business model, sprinting to liquidity, and running the marathon. What You'll Learn: Discover how founders keep their CEO positions by managing the organizational change needed to reach the next stage of scaling Read case studies that illustrate how CEOs craft growth strategies, raise capital, create culture, build their organizations, set goals, and manage processes to achieve them Discover principles of successful scaling through comparisons of successful and less successful companies Use the Scaling Quotient to assess your startup's readiness to grow Follow a road map for turning your idea into a company that can change the world.